2015
DOI: 10.14687/v12i2.3257
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between field dependent/independent cognitive styles and information & communication technologies based programs in gifted education

Abstract: The research aims to investigate gifted students' FD/FI cognitive styles and factors affecting them like preferring to take Information & Communication Technologies-based courses at gifted children's school. The study was carried out on two groups. First group consisted of 52 students identified as gifted who are attending 6th and 7th grades at the Istanbul Science & Art Center in Istanbul, Turkey, the second group consisted of 38 students who are not identified as gifted and totally the study consists of 90 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This may be due to the small sample size or suboptimal classification of cognitive style. Therefore, we applied the modified classification of cognitive style that has been used for gifted students [ 45 ] and classified our participants accordingly. Using this modified classification, we found that all of the participants significantly gained knowledge and competence after the M-TEL course regardless of cognitive style.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the small sample size or suboptimal classification of cognitive style. Therefore, we applied the modified classification of cognitive style that has been used for gifted students [ 45 ] and classified our participants accordingly. Using this modified classification, we found that all of the participants significantly gained knowledge and competence after the M-TEL course regardless of cognitive style.…”
Section: Discussionmentioning
confidence: 99%
“…The Field Dependence – Independence (FDI) concept has been subject of extensive research for over 30 years and is a well-established construct for identifying individuals’ visuospatial and perceptual processing ability (Üstünel et al, 2015). Contrary to cognition, which refers to the individual’s performance capacity and is considered to be domain-specific, cognitive learning style describes relatively stable approaches of a learner toward a learning task across a range of different domains (Kahtz and Kling, 1999) After all, cognition refers to the mental ability of acquiring information, storing it and processing it to generate new knowledge.…”
Section: Introductionmentioning
confidence: 99%